Tanggung Jawab Direksi Atas Penyalahgunaan Dana Pemegang Saham Yang Dititipkan Pada Perusahaan( Study Putusan Pengadilan Negeri Nomor 892/Pdt/2021/Pt.Sby ) - Lucy Juwita Asni; Azheri, Busyra; Fauzi, Wetria; Arben, Ali (Lareh Law Review, 2025)
A limited liability company is a legal entity that is a partnership of capital established based on an agreement, conducts business activities with a basic capital entirely divided into shares, and meets the requirements set forth in this regulations. The existence of the board of directors in the company is mandatory as their presence is crucial for managing the company in accordance with the provisions of the company law. Based on this, the author formulates the issues as follows: first, how the directors' responsibilities relate to the deposit of funds in the company by shareholders, and second, how the judges' considerations in decision number 892/Pdt/2021/Pt.Sby and decision number 39/Pdt.G/2020/Pn Btm regarding the deposit of shareholders' funds in the company. The research method used is normative juridical, which means that the board of directors is obligated to carry out their duties in good faith and with full responsibility. The theories used are first the theory of responsibility, second the ultra vires theory, and third the judge's discretion theory. The results of this research indicate that in the execution of the board of directors' duties, it should be carried out with a review of the theory of responsibility and the ultra vires theory. Conclusion on the personal responsibility of the board of directors for company losses caused by negligence in performing their duties, it is advisable for the parties to ensure the implementation of good corporate governance by strengthening the internal supervision. Keywords : Board of Directors, Limited Liability Company, Responsibilities of the Board of Directors